Diastereoselective Synthesis of Vicinally Bis(trifluoromethylated) Alkylboron Compounds through Successive Insertions of 2, 2, 2‐Trifluorodiazoethane1. Issue 51 (24th October 2014) - Molander, Gary A.; Ryu, DaWeon
Abstract The usefulness of embedded CF3 substituents within organic substructures necessitates the development of diverse methods for incorporating this functional group. A recently reported route to α‐trifluoromethylated alkylboron compounds by an α‐transfer mechanism has now been extended to the synthesis of unprecedented, vicinally ditrifluoromethylated alkylboron compounds in a diastereoselective fashion. The utility of these products is highlighted by conversion of the CB bond into other functional groups.